Hubungan Antara Pola Asuh Otoriter Orang Tua dengan Pengambilan Keputusan Karir Pada Siswa SMA Muhammadiyah 1 Surakarta - Qanita Alifatul Azzahra; Dhian Rizkiana Putri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Authoritarian parenting is a parenting pattern applied by parents in which parents impose strict rules on children and must obey and carry out orders without exception. Career decision making is an individual's thinking process when combining knowledge about themselves with knowledge about work in choosing work-related decisions. This research aims to determine the relationship between parents' authoritarian parenting style and career decision making among students at SMA Muhammadiyah 1 Surakarta. The research method used in this research is a quantitative method. The population in this study were students of SMA Muhammadiyah 1 Surakarta, while the sample in this study was 12th grade students of SMA Muhammadiyah 1 Surakarta, totaling 132 respondents. The results of the hypothesis test show that there is a significant or strong relationship but the relationship is the opposite, so this research hypothesis can be accepted. This can be seen in the correlation test results obtained with a value of r = -0.399, significance p of p = 0 (p < 0.05).